Inhibitory control is affected by reward in patients with alcohol use disorder - Li, Yalei; Cai, Xu; Liu, Yinzhao; Jia, Liping; Lu, Guohua (Frontiers in Psychiatry, 2025)
IntroductionThe present study aimed to investigate the effects of reward and punishment on inhibitory control in the alcohol use disorder (AUD) group and healthy control group.MethodsEighteen male patients with AUD and twenty-one age- and education-matched male healthy controls were recruited for the study. Participants engaged in the two-choice oddball paradigm, which included reward, punishment, and neutral conditions. Participants were asked to respond differently to standard and deviant stimuli as accurately and quickly as possible.ResultsFor reaction time measures, deviant - standard difference of the healthy control group did not show any difference; however, deviant - standard difference of the AUD group was significantly larger in the reward condition than in the neutral condition. For accuracy measures, deviant - standard difference of the healthy control group did not show any difference; however, deviant - standard difference of the AUD group was significantly larger in the neutral condition than in the reward condition, indicating a greater decline in accuracy for deviant stimuli.ConclusionOur findings demonstrated that either reward nor punishment effectively enhanced inhibitory control in AUD patients. Notably, the reward condition was associated with a further decline in inhibitory control. It is advisable to avoid relying solely on reward- or punishment-based behavioral correction strategies, as they might heighten psychological stress and negative emotions, potentially worsening deficits in inhibitory control.